Serverless Event-Stream Processing over Virtual Actors - Bernstein, Phil; Porter, Todd; Potharaju, Rahul; Venkataraman, Shivaram; Wu, Wentao (Conference on Innovative Data Systems Research (CIDR 2019), 2019)
A serverless event-stream processing service with pay-for-use and SLA's must be scalable, highly available, and low cost. In this one-page abstract, we argue that the virtual actor model is an ideal platform on which to build such a stream processing system.